The foundation of Mirogoj as central cemetery of Zagreb - Milković, Kristina (Array, 2020)
The paper presents the foundation of Mirogoj in 1876 as the central cemetery of Zagreb. Since the 1850s, Zagreb had been developing as the capital of Croatia in the modern sense of the word, as a Gründerstadt. As early as the 1860s, the public was of the opinion that a central cemetery should be established outside the city limits. This idea came to fruition in the mid-1870s, in the context of urbanization and modernization of the city. The founding of Mirogoj was an expression of modernity and self-awareness of the bourgeois society, as well as the new sensibilities and aesthetics characteristic of the 19th century.